2009
DOI: 10.1152/japplphysiol.00491.2009
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary perfusion heterogeneity is increased by sustained, heavy exercise in humans

Abstract: Exercise presents a considerable stress to the pulmonary system and ventilation-perfusion (Va/Q) heterogeneity increases with exercise, affecting the efficiency of gas exchange. In particular, prolonged heavy exercise and maximal exercise are known to increase Va/Q heterogeneity and these changes persist into recovery. We hypothesized that the spatial heterogeneity of pulmonary perfusion would be similarly elevated after prolonged exercise. To test this, athletic subjects (n = 6, Vo(2max) = 61 ml. kg(-1).min(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 53 publications
2
60
0
1
Order By: Relevance
“…Conversely, we observed acute postrace decline in vital capacity and airflow rates at midand low lung volumes. These results suggest functional changes at the level of small airways, which are compressed in the presence of interstitial pulmonary edema and/or local bronchial-bronchiolar mucosal inflammation (4,48), so far causing increasing ventilation-perfusion heterogeneity (5). Moreover, we found a correlation between the intensity of the anti-inflammatory response (IL-10 and IL-1ra) and MVV at stress, suggesting a protective anti-inflammatory cascade in well-trained athletes, as hypothesized previously (30,33).…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, we observed acute postrace decline in vital capacity and airflow rates at midand low lung volumes. These results suggest functional changes at the level of small airways, which are compressed in the presence of interstitial pulmonary edema and/or local bronchial-bronchiolar mucosal inflammation (4,48), so far causing increasing ventilation-perfusion heterogeneity (5). Moreover, we found a correlation between the intensity of the anti-inflammatory response (IL-10 and IL-1ra) and MVV at stress, suggesting a protective anti-inflammatory cascade in well-trained athletes, as hypothesized previously (30,33).…”
Section: Discussionmentioning
confidence: 92%
“…In support of this, magnetic resonance imaging (MRI) derived perfusion heterogeneity has been demonstrated to increase following prolonged exercise in healthy trained subjects (Burnham et al 2009). In contrast, whether ventilation heterogeneity increases with exercise remains speculative (Hopkins 2006;Burnham et al 2009). …”
Section: Introductionmentioning
confidence: 89%
“…Nevertheless, potential causes for this include subtle anatomical factors that limit the capacity of airways or pulmonary vessels to cope with increased flow, changes in airway or vascular tone, airway secretions, and/or mild interstitial pulmonary edema (Podolsky et al 1996;Dempsey and Wagner 1999;McKenzie et al 2005;Hopkins 2006;Zavorsky et al 2006a;Burnham et al 2009). These postulated mechanisms may give rise to changes in ventilation and/or perfusion heterogeneity (Wagner 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mild oedema in reducing exercise capacity has been questioned [43]. Experimental studies demonstrate evidence of heterogeneous lung perfusion following prolonged exercise [44]. There is evidence that hyponatraemia, which particularly occurs in marathon running, contributes to pulmonary oedema [45][46][47][48][49][50][51][52][53].…”
Section: Exercise-induced Pulmonary Oedemamentioning
confidence: 99%
“…Recent studies have shown that mean PAP-flow relationships vary from 0.5 to 3 mmHg?L -1 ?min -1 , a six-fold variation associated with PAP .40 mmHg during high-intensity dynamic exercise at cardiac outputs .25-30 L?min -1 in some athletes [65]. Normal but steep PAP-flow relationships may limit exercise capacity through excessive afterloading of the right ventricle [44]. However, redistribution of blood flow occurs [64] and pulmonary capillary pressures may still be high enough to cause capillary stress failure in highly motivated athletes.…”
Section: High-altitude Pulmonary Oedemamentioning
confidence: 99%